2006
DOI: 10.1111/j.1748-1716.2006.01526.x
|View full text |Cite
|
Sign up to set email alerts
|

Lack of contribution of P2X receptors to neurally mediated vasoconstriction in the rabbit kidney in vivo

Abstract: In the rabbit kidney in vivo, alpha,beta-mATP-sensitive receptors mediate vasoconstriction and reduce perfusion in both cortical and medullary vascular beds. However, these receptors do not mediate neurally induced reductions in renal perfusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…In accordance with the functional data describing a key role for sympathetic nerve-derived ATP in the regulation of vasa recta diameter via contractile pericytes, we have previously reported that vasa recta and associated pericytes express mRNA for P2X1, 3, and 7 and P2Y4 and 6 (Crawford et al, 2011). Interestingly, in vivo studies in rabbits conclude that P2X receptors do not contribute to neurally mediated vasoconstriction (Eppel et al, 2006a,b,c), however this is perhaps not surprising given that we have previously demonstrated much higher levels (40-fold) of P2Y (P2Y 4 and P2Y 6 ) than P2X receptor mRNA in rat isolated vasa recta, with pericytes in situ (Crawford et al, 2011); supporting sympathetically-derived ATP acting via P2Y receptors on pericytes to mediate vasoconstriction of vasa recta.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In accordance with the functional data describing a key role for sympathetic nerve-derived ATP in the regulation of vasa recta diameter via contractile pericytes, we have previously reported that vasa recta and associated pericytes express mRNA for P2X1, 3, and 7 and P2Y4 and 6 (Crawford et al, 2011). Interestingly, in vivo studies in rabbits conclude that P2X receptors do not contribute to neurally mediated vasoconstriction (Eppel et al, 2006a,b,c), however this is perhaps not surprising given that we have previously demonstrated much higher levels (40-fold) of P2Y (P2Y 4 and P2Y 6 ) than P2X receptor mRNA in rat isolated vasa recta, with pericytes in situ (Crawford et al, 2011); supporting sympathetically-derived ATP acting via P2Y receptors on pericytes to mediate vasoconstriction of vasa recta.…”
Section: Discussionmentioning
confidence: 99%
“…Tyramine-evoked vasoconstriction of vasa recta by pericytes was significantly inhibited (~50%) by the P2 receptor antagonist suramin (Figure 2C), suggesting a key role for sympathetic purinergic signaling in the regulation of MBF by renal pericytes. Interestingly, others have shown that the α-adrenoceptor antagonist prazosin greatly reduces RBF and CBF in response to renal nerve stimulation, yet MBF was both reduced and increased (Chapman et al, 1982; Eppel et al, 2004, 2006a,b,c). This may of course be due to the relative expression of α-adrenoceptors in the vasculature throughout the kidney, which was not reported by authors of these studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, by contracting renal vascular smooth muscle cells in afferent arterioles, ATP participates in renal autoregulation via activation of P2X 1 receptors (29). Presently, however, the literature regarding the role of ATP/P2 receptor interactions in renal sympathetic neurotransmission is sparse and contradictory, with some investigators concluding that ATP, via P2 receptors, is a direct cotransmitter in the renal sympathetic nervous system (62), while others conclude that ATP/P2 receptor interactions do not participate in renal sympathetic neurotransmission (14,53).…”
Section: F472mentioning
confidence: 96%
“…29 The increased RBF was significantly attenuated by the adenosine receptor antagonist, 8-(p-Sulfophenyl) theophylline, implicating A 2 receptors in the ATP-induced increase in RBF. In a subsequent study, infusion of the P2X agonist α, β-methylene ATP reduced RBF, cortical and medullary blood flow by 63, 58 and 49%, respectively without changes in mean arterial pressure, 30 suggesting that the renal vasculature is more sensitive to P2 receptor stimulation than other vascular beds. We recently applied a more selective P2X 1 and P2X 3 receptor antagonist, P 1 , P 5 -Di-inosine-5’-pentaphosphate pentasodium salt (IP5I) to assess the role of renal P2X 1 receptors in vivo .…”
Section: Atp-p2 Receptor Signaling In Renal Hemodynamicsmentioning
confidence: 88%